Cambridge Grammar for CAE and Proficiency with answers: self-study grammar reference and practice - Hewings M. Martin (Cambridge Books for Cambridge Exams)
How can you be confident that you have covered all the grammar for the CAE and Proficiency exams? Is it possible to improve your listening skills at the same time? Cambridge Grammar for CAE and Proficiency provides complete coverage of the grammar needed for both exams - and gives you plenty of exam practice as well. It also gives you the chance to hear grammar being used in realistic situations thus making it easier to remember. Presents grammar in a listening context. Contains clear and reliable grammar explanations with lots of examples Practises a range of exam tasks from both CAE and Proficiency exams Reviews quickly the grammar you should already know Includes a helpful grammar glossary Cambridge Grammar for CAE and Proficiency is informed by the Cambridge International Corpus and the Cambridge Learner Corpus to ensure that grammar is presented in genuine contexts and the book covers the errors students really make.